Choosing and Using Utility Functions in Forming Portfolios. Issue 3 (1st July 2019) - Warren, Geoffrey J.
Abstract : Utility functions offer a means to encode objectives and preferences in investor portfolios. The functions allow one to place a score on outcomes and then identify optimal portfolios by maximizing utility. The central theme of this article is that utility functions should be tailored to the investor. I discuss how an appropriate function might be chosen and demonstrate concepts for power utility and reference-dependent utility. A modeling approach is presented that may be applied without resorting to dynamic optimization. The selection of utility functions is illustrated for four investor types. Abstract : Disclosure: The author reports no conflict of interest. Editor's Note The original version had a typographical error in Figure 4B, which has been corrected in this version. Submitted 1 October 2018 Accepted 20 March 2019 by Stephen J. Brown